2022
DOI: 10.1369/00221554221083670
|View full text |Cite
|
Sign up to set email alerts
|

Histamine H4 Receptor Expression in Triple-negative Breast Cancer: An Exploratory Study

Abstract: Triple-negative breast cancer (TNBC) is an aggressive breast cancer subtype. There are neither universally accepted prognostic markers nor molecular targets related to TNBC. The histamine H4 receptor (H4R) has been characterized in TNBC experimental models, demonstrating its critical role in tumor development and progression. In this study, H4R expression was compared in breast cancer subtypes and correlated with clinical features using The Cancer Genome Atlas data (Pan-Cancer Atlas). The H4R status was furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 99 publications
0
3
0
Order By: Relevance
“…Speisky et al reported that the H4 receptor may be a useful biomarker for predicting triple negative breast cancer prognosis [ 92 ]. Based on data from the Cancer Genome Atlas, they observed that the H4 receptor is downregulated in basal-like/triple negative breast cancer compared with luminal A and normal breast-like tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Speisky et al reported that the H4 receptor may be a useful biomarker for predicting triple negative breast cancer prognosis [ 92 ]. Based on data from the Cancer Genome Atlas, they observed that the H4 receptor is downregulated in basal-like/triple negative breast cancer compared with luminal A and normal breast-like tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Its increased expression correlated with increased patient survival. It is important to emphasise that there are no specific markers in TNBC at this time [40]. During the study, mice lacking the H4R receptor had significantly less tumour growth and percentage of CD4+ tumour-infiltrating T cells.…”
Section: Correlation Between Histamine Receptors and Breast Cancermentioning
confidence: 95%
“…Moreover, histamine has reduced cell proliferation in a dose-dependent manner, by inducing cell apoptosis and senescence at a micromolar concentration through the activation of the histamine H4 receptor (H4R) in human MDA-MB-231 and murine 4T1 TNBC cells [ 15 , 16 , 17 ]. Furthermore, the expression of the four histamine receptors subtypes have been described in human BC cell lines and tumor samples [ 18 , 19 , 20 , 21 ]. Preclinical data show that histamine improved conventional antitumor therapies response in different cancer types, supporting the rationale for the use of a combination therapy with histamine.…”
Section: Introductionmentioning
confidence: 99%